2022
DOI: 10.3390/nu15010184
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Homeostasis of Amino Acids and Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) occurs in 25–40% of patients with diabetes. Individuals with DKD are at a significant risk of progression to end-stage kidney disease morbidity and mortality. At present, although renal function-decline can be retarded by intensive glucose lowering and strict blood pressure control, these current treatments have shown no beneficial impact on preventing progression to kidney failure. Recently, in addition to control of blood sugar and pressure, a dietary approach has been recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
(98 reference statements)
0
1
1
Order By: Relevance
“…A clinical study found that the level of BCAA increased in T2DM patients while gradually decreasing with the occurrence and development of kidney injury [6], with the possible reason that decreased appetite, the disorder of acidbase metabolism, and the in ammatory response affected the concentration of amino acids in DN patients. Recently, Liu et al recently reported targeting BCAA metabolism might help prevent the progression of the renal dysfunction in diabetes patients [22]. Nevertheless, our results did not the genetically causal effect between BCAA and DN.…”
Section: Discussioncontrasting
confidence: 62%
“…A clinical study found that the level of BCAA increased in T2DM patients while gradually decreasing with the occurrence and development of kidney injury [6], with the possible reason that decreased appetite, the disorder of acidbase metabolism, and the in ammatory response affected the concentration of amino acids in DN patients. Recently, Liu et al recently reported targeting BCAA metabolism might help prevent the progression of the renal dysfunction in diabetes patients [22]. Nevertheless, our results did not the genetically causal effect between BCAA and DN.…”
Section: Discussioncontrasting
confidence: 62%
“…The therapeutic potential of NO donors or agents that enhance endogenous NO production could be significant, particularly in conditions such as renal ischemia-reperfusion injury. By improving renal medullary perfusion and overall microcirculation, NO-related therapies offer a promising avenue to mitigate renal ischemic damage and improve outcomes in acute kidney injury [ 14 , 15 ]. The integration of key terms with clinical practice underscores a translational research trajectory wherein molecular insights into renal microcirculation could inform the development of innovative therapeutic strategies, such strategies would aim to modify microvascular function and architecture, ultimately improving the management of renal pathologies and enhancing patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Saprophytic bacteria in the gut can generate metabolic products derived from the diet that can influence the state of the host's cardiovascular system. As an illustration, elevated levels of amino acid metabolites like tryptophan and histidine have been linked to heightened insulin resistance and the onset of cardiovascular disease [165]. Another notable instance is imidazole propionate, a byproduct generated through histidine metabolism.…”
Section: The Relationship Of the Gut Microbiome To The Cardiovascular...mentioning
confidence: 99%
“…Since the human body does not possess TMA-lyase, the intestinal microbiota is responsible for producing all TMA. After being absorbed, TMA travels to the liver, where the liver enzyme flavin monooxygenase-3 (FMO3) oxidizes it to TMAO [165].…”
Section: The Relationship Of the Gut Microbiome To The Cardiovascular...mentioning
confidence: 99%